BODY COMPOSITION AND CHOLESTEROL OF INDIVIDUALS PANIC DISORDER: RESPONSE TO THE AN AEROBIC PHYSICAL TRAINING (Fiep Bulletin - online, 2014)
The body composition (pletismography) and the levels of cholesterol were evaluated in individuals with panic disorder (n=15) before and after 12 weeks of a program of aerobic physical training (walking/running) and compared to those of a control group (n=12) who kept their regular routine. The levels of total cholesterol, low density lipoprotein (LDL) and the body mass of the training group were significantly reduced in relation to those in the control group. The percentage of fat in the control group increased, and the percentage of free fat mass decreased with statistically significant differences. The aerobic physical training applied to individuals with panic disorder was effective in reducing their total cholesterol, LDL and body mass. It was well tolerated, and therefore could be an effective auxiliary tool in the treatment of patients with panic disorder who also have high levels of cholesterol and overweight.